Relationship between Ownership Structure and the Modes of Dividend Payment: A Study on Dhaka Stock Exchange - Amin, Mohammad Ruhul; Kafi, Md. Abdullahel; Hossain, Md. Mahabbat (Asian Business Review, 2014)
This paper investigates whether percentage of ownership controlled by the directors of companies has any association with types of dividend declared by them. Based on the data for the years 2006 to 2009 from the Dhaka Stock Exchange, this paper found that most of the companies provided stock dividends rather than cash dividends. Using Yate’s Continuity Correction Chi-square Test, this study has found existence of a significant relationship between the percentage control of ownership and types of dividend declared. Furthermore, the study indicates that the companies having ≥50% share controlled by the directors are 3 times more likely to offer stock dividends than companies having <50% control of the shares by the directors. Whereas, the companies having ≥50% control of ownership by the directors are less likely to offer cash dividends compared with <50% control of the shares by the directors.